Neuroscience and the construction of a new child in early childhood education in Indonesia: A neoliberal legacy. (July 2022) - Adriany, Vina; Newberry, Jan
Neuroscience has become a new 'truth' in early childhood education across the globe, including in Indonesia. This article aims to demonstrate how the alignment of neuroscience discourse and the legacy of neoliberalism constructs a new form of childhood in Indonesia. The conceptual framework of brain science, predicated on biological determinism, suggests that the brain will significantly influence not only children's development in the present but also will have an impact in the future. Neuroscience is also based on the idea of transparency. Beneath this conceptual framework lies the idea that a child's mind can be made visible through both technological means and standardized development measures. Global neoliberal discourse reinforces this techno-scientific approach through the concept that stimulating children's development facilitates economic growth in a country. This instrumental use of child development contrasts with the paradigm which emphasizes children's agency. This article is based on ongoing and previous fieldwork from both authors. Using Foucault's concept of discourse and disciplinary power, the authors argue that neuroscience has become the truth that hides societal issues such as poverty as well as becomes a form of surveillance that constructs a child as being open to the adult gaze and surveillance. The findings will also illuminate the tension and negotiation between local values and global values in assembling a new form of childhood in Indonesia.